Discrepancy between subjective and objective assessments of wandering behaviours in dementia as measured by the Algase Wandering Scale and the Integrated Circuit tag monitoring system. Issue 2 (12th June 2013) - Yayama, So; Yamakawa, Miyae; Suto, Shunji; Greiner, Chieko; Shigenobu, Kazue; Makimoto, Kiyoko
Abstract Aim Although wandering is one of the major research focuses of the behavioural psychological symptoms of dementia, assessment of wandering has mostly relied on caregiver‐administered questionnaires. The purpose of this study was to compare staff‐administered Algase Wandering Scale outcomes with objective temporal and spatial movement indicators obtained from the Integrated Circuit (IC) tag monitoring system. Methods Patients with dementia were recruited from a dementia care unit in Osaka, Japan in 2007. Primary nurses administered the Algase Wandering Scale, and the temporal and spatial movements of the subjects were monitored by the IC tag. Written informed consent was obtained from each subject's proxies. Results Nurses' assessments of wandering were in agreement with the IC tag outcomes only during the day shift. Spatial movements assessed by the staff did not reflect those measured by the IC tag. Conclusion This objective measurement of wandering showed the limitations in the assessment of spatial and temporal movement by the staff.